STRATEGI PERUSAHAAN DALAM MENCAPAI LABA MAKSIMUM PADA PASAR PERSAINGAN SEMPURNA (PERFECT COMPETITION) - Doli Syahputra Hasibuan; Lilis Sartika Sihite; Nurul Mardiah; Nazwa Aulia; Divo Valentino Siboro (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to examine strategies that companies can implement to maximize profits in a perfectly competitive market structure, where firms have no control over market prices. Using a library research method, this study identifies various approaches and relevant production efficiency strategies based on classical and modern economic literature. The results show that the characteristics of a perfectly competitive market—such as the large number of market participants, product homogeneity, and the freedom of entry and exit—force companies to focus on optimizing production factors and controlling costs to achieve maximum profit. Three main approaches can be used: the total, average, and marginal approaches, with the marginal approach (MR = MC) serving as the main guideline in determining the optimal output level. In addition, choosing efficient production technology, controlling variable costs, as well as innovation and quality improvement have proven to be effective strategies in maintaining competitiveness and profitability. This study concludes that allocative and productive efficiency are the main keys to a company's success in a perfectly competitive market, and adaptive internal management strategies are the determining factors in achieving maximum profit.